2020
DOI: 10.3390/nu12061812
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nutritional and Lifestyle Factors on Glioma Incidence

Abstract: Cancers are the first main cause of premature death in developed countries. Since brain tumors, especially gliomas, are the most lethal type of cancers, risk factors for their prevalence are still being discussed. Nearly 30–50% of all cancers could be prevented by proper nutritional habits and other lifestyle factors, but their influence on the tumors of the central nervous system has not been explained completely and still requires further studies. That is why we attempted to review the available research in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Inappropriate dietary habits such as long-term consumption of processed meats (grilled, smoked, cured red, and white meats) and insufficient intakes of vegetables and fruits are thought to be a risk factor for most human cancer, and glioma is no exception ( 6 ). Currently, a few studies that investigate dietary-assisted glioma therapy have found mostly positive effects ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate dietary habits such as long-term consumption of processed meats (grilled, smoked, cured red, and white meats) and insufficient intakes of vegetables and fruits are thought to be a risk factor for most human cancer, and glioma is no exception ( 6 ). Currently, a few studies that investigate dietary-assisted glioma therapy have found mostly positive effects ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in this report, there were some evidences of heterogeneity of results by study or sex [ 47 ]. Despite the role of genetic factors in the initiation and progression of glioma, it seems that several modifiable environmental factors are also involved in its incidence [ 11 ]. For instance, adherence to an anti-inflammatory or pro-inflammatory diet might influence the risk of glioma [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The modern researches represented the increasing efficacy of micronutrients through their synergistic interactions. Such interaction of nutrients displays pleiotropic effects against glioma [ 10 , 11 ]. They simultaneously affect different mechanisms involved in malignancy initial results indicating enhanced anticancer efficacy.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Glioma can be caused by genetic and environmental factors as well as improper lifestyles, such as inherited mutations, and ionizing radiation. 3 Current treatment for glioma includes surgery, radiotherapy, chemotherapy, and drug-targeted therapies. 4 However, there are still high rates of mortality and recurrence, and fatal prognosis.…”
Section: Introductionmentioning
confidence: 99%